Production and evaluation of high nutritional sheets formulated from red beetroot puree and pomegranate juice - Mamdoh Ershidat, Omar Turki; El-Sayed, Eatemad M.; Hozifa, Shaymaa A.; Ahmed El-Farsy, Marwa Fawzi; El-Mesiry, Dalia M.; ElMeslamy, Soher Abd-Elfattah; Shehata, Rehab A.; Ahmed, Marwa A.; Antar Faramawy, Asmaa; Mohamed Elsebaie, Essam (Italian Journal of Food Science, 2024)
The objective of this investigation was studying the Physicochemical characteristics and microbiological stability of five innovative fruit sheets containing red beetroot puree (RBRP) and pomegranate juice (PJ) in ratios of 100:0, 75:25, 50:50, 25:75, and 0:100 during 6-month storage at room temperature (25–30ºC). The results showed that moisture content (ranging from 14.64% to 14.96%), water activity (ranging from 0.638 to 0.642), total phenols (ranging from 18.94 to 19.20 mg GAE/g), total flavonoids (ranging from 16.50 to 16.59 mg rutin [RE]/g), 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity (ranging from 73.66% to 77.02%), and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) scavenging activity (ranging from 50.13% to 52.09%) in 100% RBRP sheets were more than in 100% PJ sheets. In contrast, 100% RBRP sheets had a lower pH (ranging from 4.09 to 4.13), total soluble solids (TSS) (ranging from 63.99 Brix to 65.08 Brix), total sugars (ranging from 59.58% to 59.90%), and hardness (ranging from 12.88 N to 14.10 N) than that of 100% PJ sheets. In addition, the findings revealed that at zero time when the replacement percentage of PJ for RBRP increased in the sheets formula from 25% to 100%, there was increase in TSS (from 65.11 Brix to 67.41 Brix), acidity (from 1.03% to 1.90%), total sugars (from 59.29% to 61.72%), and hardness (from 12.27 N to 13.85 N) as well as decrease in moisture content (from 15.01% to 14.75%), water activity (from 0.652 to 0.630), total phenols content (18.71 to 17.01 mg GAE/g), total flavonoids content (15.74 to 12.97 mg RE/g), DPPH scavenging activity (from 72.19% to 63.28%), ABTS scavenging activity (from 50.86% to 44.28%), and L* value (from 22.80 to 21.86). Significant decrease (p ≤ 0.05) was observed in pH, moisture, water activity, total sugars, total phenol contents, total flavonoid contents, and antioxidant activity during the storage period. All sheets were found to be extremely sensory-acceptable and microbiologically safe. In conclusion, RBRP and PJ or a mix of them could be used as functional sheets with high storage stability.